2014
DOI: 10.1200/jco.2013.54.4833
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide Compared With Ifosfamide in Consolidation Treatment of Standard-Risk Ewing Sarcoma: Results of the Randomized Noninferiority Euro-EWING99-R1 Trial

Abstract: Cyclophosphamide may be able to replace ifosfamide in consolidation treatment of standard-risk Ewing sarcoma. However, some uncertainty surrounding the noninferiority of VAC compared with VAI remains at this stage. The ongoing comparative evaluation of long-term renal and gonadal toxicity is crucial to decisions regarding future patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
129
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 27 publications
5
129
1
2
Order By: Relevance
“…VAC was statistically not inferior to VAI; however, 3-year EFS was slightly higher for patients receiving VAI. 39 Various dosage paradigms of VAC-IE (vincristine, doxorubicin, and cyclophosphamide, alternating with ifosfamide and etoposide) have been investigated. Although dose escalation of alkylating agents in VAC-IE did not improve outcomes for patients with localized disease, 40 chemotherapy intensification through interval compression has been shown to improve outcomes.…”
Section: Chemotherapymentioning
confidence: 99%
“…VAC was statistically not inferior to VAI; however, 3-year EFS was slightly higher for patients receiving VAI. 39 Various dosage paradigms of VAC-IE (vincristine, doxorubicin, and cyclophosphamide, alternating with ifosfamide and etoposide) have been investigated. Although dose escalation of alkylating agents in VAC-IE did not improve outcomes for patients with localized disease, 40 chemotherapy intensification through interval compression has been shown to improve outcomes.…”
Section: Chemotherapymentioning
confidence: 99%
“…[4][5][6] Multimodal therapy includes systemic therapy as well as surgery and radiotherapy (RT). 7 Until now, clinical trials on ES have principally focused on a comprehensive investigation of systemic treatment.…”
mentioning
confidence: 99%
“…Recent clinical studies which combined these modalities have shown survival rates of near 80% 8,9 although results from our country were slightly inferior 10 . Local control of the tumor in patient with ES is tried to be ensure with surgery and/or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%